Women Leadership in Local Wisdom Perspective: Bugis Muslims Scholars’ Thought and Bugis Culture - Muhammad Yusuf (Analisa: Journal of Social Science and Religion, 2015)
This research is an effort to explain quranic values in collaborating and synergizing with the values of local wisdoms which influences social life paradigm. The main resources of this research are the  thought of Bugis Muslim scholars in the Quranic exegesis which is in Bugis language. This exegesis was written by MUI of South Sulawesi consisting of 11 volumes. This study concerns on the interpretation of verses on women leadership which is then connected with the cultural values of Bugis society. Data on cultural values were collected through interview and observation. Bugis ulama tend to follow the perspective of Middle Eastern ulama regarding the issue of leadership in the domestic area, they argue that man is the leader. Meanwhile the cultural values ‘sibaliperri, sipurepo’ indicate that husband and wife are partners in dealing with the family matters.  In the public space, Bugis ulama agree with the Bugis culture in which they say that women have opportunities to handle various tasks either at an organization or community.